Candidatus Liberibacter asiaticus: An important factor affecting bacterial community composition and Wolbachia titers in Asian citrus psyllid - Jiang, Rui-Xu; Shang, Feng; Jiang, Hong-Bo; Dou, Wei; Cernava, Tomislav; Wang, Jin-Jun (Frontiers in Microbiology, 2023)
Endosymbionts play crucial roles in various physiological activities within insect hosts. The Asian citrus psyllid (ACP), Diaphorina citri Kuwayama, is an important vector for Candidatus Liberibacter asiaticus (CLas), a fatal pathogenic bacterial agent causing the disease Huanglongbing in the citrus industry. This study combines high-throughput sequencing of 16S ribosomal RNA amplicons to explore how CLas affects the bacterial community in different color morphs (blue, gray), genders, and tissues (cuticle, gut, mycetome, Malpighian tubule, ovary, and testis) of ACP. We found that there was no significant differences in the bacterial community diversity and infected CLas ratio between the different color morphs and genders of ACP adults. However, acquiring CLas could promote the adult bacterial community’s diversity and richness more than in the uninfected condition. The presence of CLas could increase the Wolbachia and Enterbacteriaceae proportions more than in the uninfected condition. The bacterial community diversity in the CLas infected tissues of ovary and cuticle was lower than the uninfected condition, but the richness of all tissues was not different between the infected and uninfected conditions. CLas could also change the different tissues’ bacterial structure and make the bacterial relationship network simpler than it is in an uninfected condition. Furthermore, we used quantitative real-time PCR to assess the dynamic changes of Wolbachia in uninfected and infected color morphs and tissues of ACP. The results showed that Wolbachia titers were significantly higher in infected adults than in uninfected adults. In different tissues, the Wolbachia titers in the testis, ovary, and Malpighian tubule were higher than their uninfected counterparts. Our results provide essential knowledge for understanding the symbionts of the ACP and how CLas affects the bacterial community of the ACP.